Relationship between serum 25-hydroxyvitamine D and non-alcoholic fatty liver disease - S.M. Tkach; V.I. Pankiv; A.E. Dorofeev (Mìžnarodnij Endokrinologìčnij Žurnal, 2023)
Background. Today, non-alcoholic fatty liver disease (NAFLD) is a very common condition that affects ~ 25 % of the world’s population. The prevalence of NAFLD is expected to increase further in the coming years due to the obesity pandemic, rising incidence of diabetes and other factors. The search for modifiable risk factors for NAFLD is relevant and urgent to prevent the spread, morbidity and progression of this disease. Recent studies have shown that vitamin D may be a risk factor, which, due to its pleiotropic effects, modulates liver inflammation and fibrogenesis and can improve the liver response to insulin. But there is no definitive opinion on the relationship between vitamin D level and the risk of NAFLD. The purpose of the study was to investigate the serum level of 25(OH)D in patients with NAFLD and to establish its possible relationship with the development and progression of this disease. Materials and methods. A total of 120 patients (78 women, 42 men) with a diagnosis of NAFLD aged 18 to 60 years were examined. The diagnosis of NAFLD was made based on multimodal ultrasound with steatometry and elastography, increased transaminases in 2 or more measurements, the presence of risk factors such as type 2 diabetes mellitus and/or obesity. Serum 25-hydroxyvitamin D deficiency was considered at its serum level ≥ 20 and < 30 ng/ml, and deficiency at < 20 ng/ml. Results. The mean level of 25-hydroxyvitamin D (25.7 ± 2.6 ng/ml) in all patients with NAFLD was significantly and reliably lower than in the control group (52.2 ± 6.8 ng/ml, P < 0.01), and in people with non-alcoholic steatohepatitis (NASH), it was lower than in those with simple steatosis (24.3 ± 3.0 vs. 27.1 ± 2.2), although the difference was non-significant (P > 0.05). In patients with NASH and liver fibrosis, the mean level of 25-hydroxyvitamin D was also lower than in all patients with NAFLD/NASH, especially in severe F3–4 fibrosis, although this difference was also non-significant. Normal vitamin D status was observed in only 42 (35 %) patients with NAFLD/NASH, while most people (78 patients, 65 %; P < 0.005) had a decrease in serum vitamin D levels in the form of its insufficiency or deficiency: 66 (55 %) and 12 individuals (10 %), respectively. Conclusions. An open-label study found an inverse relationship between 25(OH)D levels and the risk of NAFLD development and progression. Because vitamin D is considered a modifiable risk factor for NAFLD, this finding may be of clinical significance due to the possible preventive effect of vitamin D in this disease.